First positronium lifetime imaging with scandium-44 on a long axial field-of-view PET/CT - Mercolli, Lorenzo; Steinberger, William M.; Grundler, Pascal V.; Moiseeva, Anzhelika; Braccini, Saverio; Conti, Maurizio; Moskal, Paweł; Rathod, Narendra; Rominger, Axel; Sari, Hasan; Schibli, Roger; Seifert, Robert; et al. (Frontiers in Nuclear Medicine, 2025)
PurposeThe physical properties of 44Sc, combined with its imminent clinical application, position it as a prime candidate for in vivo positronium lifetime imaging. In this study, we investigate the count statistics for ortho-positronium (oPs) measurements with 44Sc on a commercial long-axial field-of-view (LAFOV) PET/CT.MethodA NEMA image quality phantom was filled with 41.7 MBq of 44Sc dissolved in water and scanned on a LAFOV PET/CT. Three-photon events were identified using a prototype feature of the scanner and dedicated software. The lifetime of oPs was determined in the phantom spheres and in 4×4×4 mm3 voxels.ResultsAll measured oPs lifetimes are compatible, within the uncertainties, with the literature values for water. The oPs lifetime is 2.65±0.50, 1.39±0.20 and 1.76±0.18 ns in the three smallest spheres of the phantom and 1.79±0.57 ns for a single voxel in the central region of the largest sphere. The relative standard deviation in the background regions of the time difference distributions, i.e., for time differences smaller than −2.7 ns, is above 20%—even for voxels inside the phantom spheres.ConclusionsDespite the favorable physical properties of 44Sc, the count statistics of three-photon events remains a challenge. The high prompt-photon energy causes a significant amount of random three-photon coincidences with the given methodology and, therefore, increases the statistical uncertainties on the measured oPs lifetime.